Higher Education Financing Model Through Cash Waqf: An Exploratory Study - Deden Misbahudin Muayyad; Didik Jatmiko (Department of Islamic Economics, Islamic University of Indonesia, 2021)
The purpose of this study was to analyze the financing model for higher education through cash waqf. The data used is primary data obtained from the results of interviews (in-depth interviews) with experts who have an understanding of the problems discussed. The number of participants required is 3 participants. In addition, data was collected from a library review. The analytical method used in this study used a qualitative method with the help of atlas ti software. The results of the study indicate that in an effort to support sustainable higher education, it is necessary to establish a cash waqf institution managed by the higher education, after that cash waqf funds can be used for the purposes of higher education institutions such as student scholarships, allowances for lecturers and education staff, facilities and infrastructure, and investment.